IRETA video library - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
With funding provided by CTA, the institute for Research, Extension and Training in Agriculture (IRETA) now has an operational video programmes production facility. The video library currently holds over 150 title, and a catalogue is available from...